VISUAL EXPLORATION OF HISTORIC BUILDINGS IN SEMARANG'S OLD TOWN IN WATERCOLOR DIGITAL ILLUSTRATION ART - Fakhrudin; Mujiyono (Eduarts: Jurnal Pendidikan Seni, 2025)
Semarang, the capital of Central Java Province, boasts a rich history embodied in its cultural heritage dating back to the colonial era. The Old Town area, home to numerous historic buildings, served as inspiration for this creation, exploring the historical value of its aesthetic architecture. Besides attracting tourists, this area holds profound meanings that deserve appreciation. Using digital watercolor illustration techniques, this design seeks to revive the community's collective memories and strengthen appreciation for their cultural heritage. Through an emotional and illustrative approach, this artwork serves as both a visual representation and an educational medium, raising awareness of the preservation of historic buildings amidst the tide of modernization. The required tools are an iPad Pro 11, Apple Pencil, and Procreate software. The materials used are ivory paper. The techniques used involve digital media; the process of creating, coloring, and arranging images is carried out using digital devices and applications such as the iPad and Procreate. The creative process for this study project included pre-production, production, and post-production. The resulting design is a digital illustration artwork featuring the Blenduk Church and the Marba Building. This work demonstrates that digital illustration can be an effective tool for preserving local historical and cultural values.